The Effect of Immigrant Customer Service Representatives’ (ICSRs) Accents on Customers’ Experience and Satisfaction - Utulu, Anthony U. (European Scientific Journal, ESJ, 2023)
This study shows that most customers are frustrated because of the unintelligible communication they usually have with Immigrants Customer Service Relations (ICSRs). Customers’ experience worsens when they find it difficult to understand the customer representatives they are communicating with because their accents make them unintelligible, causing communication breakdown. This study adopted the qualitative research approach. Frame Analysis (FA) and Discursive Social Psychological (DSP) methods were used to analyze Reddit online forum users’ responses to a peer’s question posed on the forum. It found that accents play a significant role in why some customers, using American customers as cases, are rude to ICSRs. Aside from this, it also found that other factors, such as the organizations’ systems—long wait times to access CSRs, network connection failures, inexperienced CSRs, and acts of racism affect customer experience.